Alan Sorrell. The man who created Roman Britain - Sorrell, Julia (Oxbow Books, 2018)
Alan Sorrell's archaeological reconstruction drawings and paintings remain some of the best, most accurate and most accomplished paintings of their genre that continue to inform our understanding and appreciation of historic buildings and monuments in Europe, the Near East and throughout the UK. His famously stormy and smoky townscapes, especially those of Roman Britain, were based on meticulous attention to detail borne of detailed research in collaboration with archaeologists such as Sir Mortimer Wheeler, Sir Cyril Fox and Sir Barry Cunliffe, who excavated and recorded his subjects of interest. Many of his reconstructions were commissioned to accompany visitor information and guidebooks at historic sites and monuments where they continue to be displayed. But archaeological subjects were not his only interest. His output was prodigious: he painted murals, portraits, imaginative and romantic scenes and was an accomplished war artist, serving in the RAF in World War II. In this affectionate but objective account, Sorrell's children, both also artists, present a brief pictorial biography followed by more detailed descriptions of the genesis, research and production of illustrations that demonstrate the artist's integrity and vision, based largely on family archives and illustrated throughout with Sorrell's own works. So influential were Sorrell's images of Roman towns such as London, Colchester, Wroxeter, St Albans and Bath, buildings such as the Heathrow temple and the forts of Hadrian's Wall, that he became known as the man who invented Roman Britain.